Nutrient Management for yield and quality improvement in Kacholam - Kavitha P.R (Department of Agronomy, College of Horticulture, 2012)
Kacholam (Kaempferia galanga L.) is an important medicinal and aromatic plant of the Zingiberaceae family. In India, kacholam is cultivated throughout the plains for the rhizomes. The economic produce of kacholam is the chopped and dried rhizomes of 6-7 months maturity. Dried rhizomes are used in bulk quantities in ayurvedic medicine and in the cosmetic industry. It is used for curing inflammatory wounds, skin disorders, piles, oedema, fever, epilepsy, splenic disorders and asthma. The constituents of the rhizome oil include para methoxy ethyl cinnamate (60.24 % of the oil), ethyl cinnamate (20.66%), cineol, borneol, 3-carene, camphene, kaempferol, kaempferide and cinnamaldehyde. There is immense scope for cultivation of kacholam in Kerala, as the climatic and soil conditions are optimally suited to its growth and development. Kacholam can be grown as an intercrop in coconut gardens and it has attained the status of a cash crop of homesteads. Though there is an approved ad hoc recommendation of organic manures as well as N, P and K for kacholam, there are reports that the K dose is inadequate. Also, considering the low availability and high cost, the present organic manure recommendation of 20 tonnes ha-1 is rather unaffordable. There are also reports about the inadequacy in the availability of secondary nutrients viz., S, Ca and Mg, which may affect yield and quality of kacholam. A field experiment was conducted during 2011-2012 in the coconut garden of Water Management Research Unit, Vellanikkara to evaluate the effect of varying doses of K and secondary nutrients on yield and quality of kacholam. There were 12 treatments with 3 replications each. Treatments consisted of package of practices (POP) recommendation of 20 tonnes farmyard manure along with 50:50:50 kg N, P and K ha-1 and combinations with S, Ca, Mg and extra dose of K applied as first and second top dressing. Rhizomes were planted at a spacing of 20 x 15 cm and planting was done on 3/ 06/ 2011. Harvesting was done seven months after planting. Observations included biometric observations taken at monthly intervals, nutrient contents at 2 ½ and 5 months after planting, and at harvest. Nutrient uptakes was also worked out. Essential oil and oleoresin in rhizomes were also analysed. The soil pH and chemical parameters were analysed before and after the experiment. There were significant differences among treatments with respect to yield, essential oil, oleoresin, nutrient contents and nutrient uptake. With respect to yield, the treatment receiving S applied either at first top dressing or at second top dressing and that with S, Ca and Mg recorded highest yields as compared to other treatments. Essential oil content also showed the same trend as that of yield. But in case of oleoresin, the content was more only in the treatments receiving S as first and second top dressing. This treatment resulted in highest uptake of all nutrients except Ca at harvest. Application of the secondary nutrients thus had a direct positive effect on yield and quality. Changing the N:K ratio of present NPK recommendation resulted in reduction of yield and other quality parameters. The yield and quality parameters with the reduced organic manure dose were found similar to the present POP. Increased phosphorus content of soil observed after experimentation indicated the possibility of reducing the recommended phosphorus dose. Supplementing S, Ca and Mg with a reduced organic manure dose is also to be tested.